A fuzzy regression causality approach to analyze relationship between electrical consumption and GDP. (15th January 2022) - Pandelara, Diego; Kristjanpoller, Werner; Michell, Kevin; Minutolo, Marcel C.
Abstract: The debate on the energy-growth nexus has been revisited widely in the research literature focusing on the causal relationship between energy consumption and Gross Domestic Product. The research stream has not resulted in optimal policy recommendations since the results are ambiguous and mixed. In this study, a wavelet approach with fuzzy regression analysis describes the fuzzy causal relationship between energy consumption and Gross Domestic Product for different timescales of 61 countries between 1990 and 2014. The results allow for policy-making according to the fuzziness description of the data and different timescales. A focused analysis of each country is conducted according to the associated continent and Human Development Index classification to contrast the results. Highlights: Energy consumption-economic growth nexus differs by country. Four theories about the energy consumption-economic growth nexus are tested. Wavelet transform with fuzzy regression captures differences in energy consumption-economic growth by country. Index of Confidence developed to test fuzzy regression model improvement.